The Role of Hindu Extension Workers in Improving Yowana Jagra Winangun Religious Attitudes in Amertasari Traditional Village, Pegayaman, Sukasada District, Buleleng Regency - Duwika, Kadek (Jurnal Ar Ro'is Mandalika (Armada), 2022)
Ametasari Traditional Village Pegayaman Village is one of the villages located in Amertasari Village Pegayaman Village where the majority of the population is Muslim. Amertasari Traditional Village has a population of 60 Families who carry Pura Kahyangan Tiga as in other Traditional Villages. The role of Religious Extension in Amertasari Pegayaman Traditional Village, Sukasada Subdistrict, Buleleng Regency is expected to provide religious guidance to the Yowana Jagra Winangun whose educational condition is very worrying in continuing future development, especially in the Amertasari Traditional Village pegayaman village. The number of Yowana who do not want to continue their education to a higher level such as Strata one or Strata two. Especially in economic conditions that are still fitting pasan. In improving the quality of human resources is considered necessary hindu extension that is able to change the mindset of the Yowana in the Village Amertasari Pegayaman. So the presence of extension is highly anticipated by yowana in Amertasari Pegayaman Traditional Village. Although many factors are an obstacle in carrying out counseling to the Yowana Jagra Winangun will not be a problem for the extension to still provide motivation and better hope for the future of the Yowana Amertasari Indigenous Village.